Manuscript verse collectors and the politics of anti-courtly love poetry - Eckhardt, Joshua (Oxford : Oxford University Press, 2009)
This is an analyis of the contribution to literary history of early 17th century hand-written English poetry anthologies. Compiled by manuscript verse collectors, these anthologies preserved a number of pieces by major authors of the English Renaissance, yet they tended to surround them with unprintable verses on sex and politics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Love poetry, English -- History and criticism; English poetry -- Early modern, 1500-1700 -- History and criticism; Manuscripts, English (Middle) -- Collectors and collecting; Politics and literature -- England -- History -- 17th century